Bounds of Mean Code Word Lenth With Generalized Information Measure and its Application in Coding Theory - Litegebe Wondie; Satish Kumar (International Journal of Mathematics And its Applications, 2019)
In this communication, we find a lower and upper bounds for mean code word length for complete and incomplete probability distribution with generalized information measure and we identify its application in coding theory.